Speech Acts Proficiency of Junior High School English Teachers - Kamarudin Kamarudin; Lume Lume (Universitas Islam Negeri (UIN) Mataram, 2018)
Junior High School English teachers involved in this study taught English‘ speech acts at a Junior High School, where the materials taught include high level of spoken English. Thus, the English teachers need to be proficient in this particular skill. As professional educators, the teachers must have professionalcompetencies, particularly a good comprehension of the materials. Speech act constitutes spoken English, which is generally taught in Junior High School. Developing communication competence in English is the main purpose of English teaching in Junior High School. This descriptive qualitative research aims to describe a phenomenon: the ability of speech acts of Junior High School teachers. This knowledge comprises of several categories, namely the ability to define of speech acts, to identify speech acts conversations and to figure out speech act utterances. Drawing on the data garnered through the interviews, it was unveiled that most of the Junior High School English teachers could respond the given questions pertinent to speech acts. They could define the meaning of speech acts, identify the speech act conversations and figure out the speech act utterances. This study demonstrates that the proficiency level of the Junior High School English teachers is very good as they comprehend teaching materials and have good pedagogical skills.